The evaluation level of carboxyhemoglobin in children blood<3y-14y> with chief complain of headache, nausea, and dizziness referring to pediatric clinics of Loghman hakim hospital in year 2018-2019 - Taraz, Maryam; Farnaghi, Fariba; Hassanian-Moghaddam, Hossein; Gachkar, Latif (Researcher Bulletin of Medical Sciences, 2021)
Carbon monoxide poisoning is common, challenging and serious poisoning with wide range of non-specific flu-like clinical manifestations that leads to misdiagnosis. This cross-sectional descriptive controlled study conducted in Loghman Hakim Hospital on 3-14 year-old patients presenting with non-specific Flu-like (headache, dizziness, nausea, vomiting, malaise) symptoms from November 2018 to May2019. In all subjects carboxyhemoglobin level measured via noninvasive pulse CO-oximetry (Massimo Company, USA). Demographic data, cigarette, shisha, opium smoke exposure, type of home heater, carboxyhemoglobin level were collected and statistically analyzed via SPSS v16.0. A total of 93 children 3-14 year-old were enrolled the study. Their mean age was 4.6+4.3 years, 46% were male and54% female. Mean carboxyhemoglobin level was 27.8+9.7 %( range 2.7% to 44%). The most frequently encountered symptoms were nausea &vomiting (44%), dizziness (36%), headache (32%) and myalgia (23%). We obtained the COHb levels using noninvasive pulse oximeter for all study patients and their mother, and the levels > 5% for non-smokers were considered as CO poisoning. Of the 93 study patients, 49%had normal carboxyhemoglobin levels (CoHb level< 5%). Of the remaining 51% study patients, 47 patients had CoHb levels between 5% and 10%, and seven patients > 10%. Closer attention to early and nonspecific signs and symptoms of Carbon Monoxide poisoning and higher clinical suspicion could reduce the rate of misdiagnosis and therefore minimize complications in this serious poisoning.